Curriculum proposal to accelerate learning for some offensive skills basketball The first phase for the students - Faculty of Physical Education - hamed, hudi; ali , ishraq (Journal of Physical Education, 2012)
The aim of the research is to develop curriculum to accelerate the learning process for some of the skills of offensive basketball that the first phase of join-time official in late year and this problem is reflected negatively on the learning process, and make research on a sample of students in the first stage reached (20) a student has used the researchers means of appropriate statistical They concluded: - The presence of significant differences between pre and post test for the sample and for the post-test and all the research variables.